Intention and Its Impact on Islamic Financial Transactions: a Phenomenological Approach to Monotheism - Bulutoding, Lince; Rahma Sari, Nur; Ruqayyah Yunus, Ayu (Universitas Islam Negeri Alauddin Makassar, 2024)
The aim of this research is to identify the impact of intentions in Islamic financial transactions at Bank Syariah Indonesia (BSI). Intention in Islamic financial transactions is a component that determines whether a behavior is good or bad. Intention in Islam indicates the validity of an action. As explained in QS. Al-Isra' verse 19 and the Hadith of the Prophet Muhammad saw which explains that intentions have an impact on a Muslim's financial transactions which will also have an impact on the organization. The research method used in this research is qualitative with a monotheism phenomenological approach. The data source uses noema and noesis data, while data analysis uses intentional analysis. The informants in this research were 4 people who represented BSI financial managers. The research results explain that intentions in Islamic financial transactions can become a collective intention at BSI. There are 3 elements in intention, namely: knowledge of faith in transactions, knowledge of sharia and feelings of ihsan in managing finances. This intention can animate management in managing financial transactions of Islamic entities. Intention can encourage the accountant's determination to make financial reports honestly, fairly, responsibly and comply with sharia accounting standards